2013
DOI: 10.1366/12-06860
|View full text |Cite
|
Sign up to set email alerts
|

On the Exploitation of Mid-infrared Iridescence of Plumage for Remote Classification of Nocturnal Migrating Birds

Abstract: A challenging task in ornithology lies in identifying high-altitude nocturnal migrating bird species and genders. While the current approaches including radar, lunar obscuration, and single-band thermal imaging provide means of detection, a more detailed spectral or polarimetric analysis of light has the potential for retrieval of additional information whereby the species and sex could be determined. In this paper, we explore remote classification opportunities provided by iridescent features within feathers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 106 publications
(123 reference statements)
0
15
0
Order By: Relevance
“…We have earlier shown how detailed wing beat waveforms in several spectral bands can yield remote microscopic information in bird feathers [5]. Equivalently, remote nanoscopy may be conducted of insect wing membranes using multi-band lidars, which, so far, have been developed for conventional aerosol particle characterization [17,18].…”
Section: Classification and Information In Oscillatory Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…We have earlier shown how detailed wing beat waveforms in several spectral bands can yield remote microscopic information in bird feathers [5]. Equivalently, remote nanoscopy may be conducted of insect wing membranes using multi-band lidars, which, so far, have been developed for conventional aerosol particle characterization [17,18].…”
Section: Classification and Information In Oscillatory Particlesmentioning
confidence: 99%
“…While research in the area of radar entomology has been conducted over several decades and numerous interesting applications have been described [4], laser radar (light detection and ranging; lidar) systems in the optical regime have the potential of achieving a far better sensitivity and address and classify even the tiniest insects, simply because most insects are much smaller than the wavelengths of microwaves used in radars but larger than the wavelengths of light. Further, optical off-the-shelf components allow spectral-and polarimetric target classification, providing molecular as well as microstructure information [5,6]. Along these lines our group has previously demonstrated lidar remote detection of insects labeled with fluorescent powders, e.g., for assessing dispersal rates on a landscape scale [7,8].…”
mentioning
confidence: 98%
“…Classification of spatial reflectance patterns using PCA-based similarity factors can be applied to similar animal species when the effects of disorder and spatial averaging over repeated nanostructures contribute to smooth angular color variations [1,9,11]. However, there are iridescent birds and other animal species that have tetrachromatic vision, from the UV to the visible region, and show polarization effects and reflection maxima in the UV [1, 14-17, 19, 20, 43] and in the IR spectra [15,22,25]. This issue remains open and requires multispectral or hyperspectral polarization imaging methods in those spectral ranges [22,25].…”
Section: Resultsmentioning
confidence: 99%
“…Harvey et al have investigated the dependence between scattered light and orientation of feather barbs of the Purple Glossy Starling (Lamprotornis purpureus) and the African Emerald Cuckoo (Chrysococcyx cupreus) using a imaging scatterometer based on a spherical gantry configuration and an RGB camera [23,24]. Brydegaard et al have investigated the existence of iridescent effects in the mid-IR region of many avian species for remote classification at long distances [25]. They have concluded that these IR iridescent features have a structural origin at the micrometer level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation